Thermochemical liquefaction of wheat straw in sub- and supercritical tetralin - Evstaf‘ev, S. N.; Fomina, E. S.; Tiguntceva, N. P. (Proceedings of Universities. Applied Chemistry and Biotechnology, 2022)
The present work investigates the thermochemical conversion of wheat straw biomass in a suband supercritical tetralin medium. The experiment was carried out in a batch reactor at 285, 330, 380, 420 and 460 °C for 10 minutes. The process of straw liquefaction in subcritical tetralin was characterised by relatively high efficiency. At 420 °C, the biomass conversion rate amounted to 98.2% a.d.m. The maximum yield of liquid products during liquefaction (81.6% a.d.m.) was obtained at 380 °C. The liquid products were fractionated by successive extraction with hexane, water and ethanol. According to GC-MS data, the liquefaction products soluble in hexane comprised a mixture of low-molecular weight degradation products of straw components and tetralin derivatives, including methyl esters of fatty acids, aromatic compounds, alkanes and minor alcohols and ketones. When the process temperature increased, the content of esters diminished, followed by an increment in the proportion of aromatic compounds up to 50% rel. No esters and phenolic compounds were present in the liquefaction products soluble in hexane obtained at 460 °C. Dehydrogenation, alkylation and isomerisation of tetralin with the formation of naphthalene, 1,4-dihydronaphthalene and alkyl derivatives of tetralin, naphthalene and indane occurred under the given conditions. The conducted comparative analysis of infrared spectra for straw and solid products of liquefaction suggested that, at temperatures of up to 330 °C, the process of polysaccharide fragmentation is more pronounced in the straw biomass, while, at higher temperatures, the process of lignin fragmentation prevails. As a result, the IR-spectrum of the solid product obtained at 380 °C revealed weakly pronounced absorption bands of alkylaromatic structural fragments. At the same time, only the absorption bands of mineral components in straw ash and adsorbed water were observed in the IR-spectrum of the solid product obtained at 420 °C.